ÐœÐ¾Ð¶Ð»Ð¸Ð²Ñ–ÑÑ‚ÑŒ ÐºÐ¾Ñ€ÐµÐºÑ†Ñ–Ñ— Ð¿Ñ€Ð¾Ñ†ÐµÑÑƒ Ð¿ÐµÑ€Ð¾ÐºÑÐ¸Ð´Ð°Ñ†Ñ–Ñ— Ð² Ð¾Ñ€Ð³Ð°Ð½Ñ–Ð·Ð¼Ñ– Ñ‰ÑƒÑ€Ñ–Ð² Ð·Ð° ÑƒÐ¼Ð¾Ð² Ñ…Ð¾Ð»Ð¾Ð´Ð¾Ð²Ð¾Ð³Ð¾ ÑÑ‚Ñ€ÐµÑÑƒ - Petrun, L. M. (Publishing House ‘Akademperiodyka’ of the National Academy of Sciences of Ukraine; Institute for Problems of Cryobiology and Cryomedicine, 2008)
Intensity of lipid peroxidation in thymus rat enzymatic fraction at cold stress (4Â°C) was investigated. It was shown that with small doses of polyamines it was possible to decrease peroxidation processes of an organism.